2012
DOI: 10.1111/j.1600-0501.2012.02488.x
|View full text |Cite
|
Sign up to set email alerts
|

GSK3b‐inhibitor lithium chloride enhances activation of Wnt canonical signaling and osteoblast differentiation on hydrophilic titanium surfaces

Abstract: Stimulation of the canonical Wnt pathway promoted osteoblast differentiation on hydrophilic modSLA surfaces. Taken together, these results demonstrate that Wnt activators such as LiCl should be further tested as a possible approach to improve implant osseointegration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 25 publications
3
62
0
3
Order By: Relevance
“…This behavior started to manifest itself from early time-points, up to 3 h after seeding, and became more evident by 24 h of culture, a time-point by which adhesion is considered mostly stable. Even on substrates with low roughness such as Pickled surfaces, where cells exhibit differentiation behaviors quite distinctively different from SLA discs 1) , cells preferentially adhered to titanium peaks, and areas of the surface near to peaks (Fig. 6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior started to manifest itself from early time-points, up to 3 h after seeding, and became more evident by 24 h of culture, a time-point by which adhesion is considered mostly stable. Even on substrates with low roughness such as Pickled surfaces, where cells exhibit differentiation behaviors quite distinctively different from SLA discs 1) , cells preferentially adhered to titanium peaks, and areas of the surface near to peaks (Fig. 6).…”
Section: Discussionmentioning
confidence: 99%
“…Micro-structured surfaces have long been used to promote the integration of endosseous implants in bone, as rough surfaces have been extensively shown to improve the differentiation of mesenchymal and bone cells, bolstering the expression of osteoblast-specific genes [1][2][3][4] . Adhesion is a key factor in determining the ability of a cell to effectively colonise a biomaterial, and thus to deposit a matrix that can serve as basis for newly formed tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The use of the enhancer Wnt/beta-catenin lithium can be discussed in ALS in which the Wnt/beta-catenin pathway has been shown to be upregulated in several animal studies [32][33][34][35]. GSK-3beta-inhibitor lithium chloride enhances activation of the canonical Wnt signaling [42][43][44]. Lithium activates downstream components of the Wnt signaling pathway in vivo, leading to an increase of the beta-catenin protein.…”
Section: Als and Riluzolementioning
confidence: 99%
“…24,25 Moreover, recent studies reported that the ionic products and surface topography of bioactive materials could promote osteoblast differentiation of human MSCs via activation of canonical Wnt signaling pathway. 14,[26][27][28] But whether the canonical Wnt signaling pathway is responsible for the osteogenic and cementogenic effect of mnHAs on human periodontal ligament derived stem cells (hPDLSCs) has not been reported previously and needs to be verified.…”
Section: Introductionmentioning
confidence: 99%